ChemInform Abstract: A Short and Safe Method for the Synthesis of [1, 2, 5]Oxadiazolo[3, 4‐c]pyridine. Issue 35 (September 2015) - Chmovzh, Timofey N.; Konstantinova, Lidia S.; Struchkova, Marina I.; Rakitin, Oleg A.
Abstract The first synthesis of an unsubstituted oxadiazolopyridine (III) avoiding the use of explosive azidopyridines is given.